Neuroinflammation as a Factor of Neurodegenerative Disease: Thalidomide Analogs as Treatments - Jung, Yoo Jin; Tweedie, David; Scerba, Michael T.; Greig, Nigel H. (Frontiers in Cell and Developmental Biology, 2019)
Neuroinflammation is initiated when glial cells, mainly microglia, are activated by threats to the neural environment, such as pathogen infiltration or neuronal injury. Although neuroinflammation serves to combat these threats and reinstate brain homeostasis, chronic inflammation can result in excessive cytokine production and cell death if the cause of inflammation remains. Overexpression of tumor necrosis factor- (TNF-α), a proinflammatory cytokine with a central role in microglial activation, has been associated with neuronal excitotoxicity, synapse loss, and propagation of the inflammatory state. Thalidomide and its derivatives, termed immunomodulatory imide drugs (IMiDs), are a class of drugs that target the 3’-untranslated region (3’-UTR) of TNF-α mRNA, inhibiting TNF-α production. Due to their multi-potent effects, several IMiDs, including thalidomide, lenalidomide, and pomalidomide, have been repurposed as drug treatments for diseases such as multiple myeloma and psoriatic arthritis. Preclinical studies of currently marketed IMiDs, as well as novel IMiDs such as 3,6’-dithiothalidomide and adamantyl thalidomide derivatives, support the development of IMiDs as therapeutics for neurological disease. IMiDs have a competitive edge compared to similar anti-inflammatory drugs due to their blood-brain barrier permeability and high bioavailability, with the potential to alleviate symptoms of neurodegenerative disease and slow disease progression. In this review, we evaluate the role of neuroinflammation in neurodegenerative diseases, focusing specifically on the role of TNF-α in neuroinflammation, as well as appraise current research on the potential of IMiDs as treatments for neurological disorders.